Design and Implementation of IoT-based Digital Notice Board using Arduino Uno - Saumendra Behera,MonalisaSamal (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
In this paper, the implementation of simple and IoT based wireless notice board is presented. The proposed system uses Wi-Fi for communicating with cloud data base. The idea of digital notice board and it’s working starts from pushing a message to cloud using an android mobile. At the received end aArduino Uno with a valid internet connection is setup is deployed and it is ready to receive the messages. Whenever it receives a new message it alerts the LCD display connected to it and it displays the message on LCD display.